Canine distemper virus in a crab-eating fox (Cerdocyon thous) in Brazil: Case report and phylogenetic analyses - Megid, Jane [UNESP]; De Souza, Vanessa Aparecida Feijó [UNESP]; Teixeira, Carlos Roberto [UNESP]; Cortez, Adriana; Amorin, Renée Laufer [UNESP]; Heinemman, Marcos Bryan [UNESP]; Cagnini, Didier Quevedo; Richtzenhain, Leonardo José (Wildlife Disease Association, 2009)
Although canine distemper is enzootic worldwide and has a wide host range, there are no reports of canine distemper virus in crab-eating foxes (Cerdocyon thous) that Erovide information on virus phylogeny and istopathologic lesions. The objective of this study is report and describe canine distemper in a crab-eating fox (C. thous), with a focus on the phylogeny of the virus strain and the histopathologic lesions in the animal. © Wildlife Disease Association 2009.
Keywords: Cerdocyon thous; Clinical signs; Histopathology; Nervous system; Virus phylogeny